EFFECT OF FARMYARD MANNURE, GREEN MANNURE AND FERTILIZER LEVELS ON SEED POTATO PRODUCTION IN NORTH-WESTERN HILLS - Sharma, Ashwani Kumar; Singh, Sarjeet (Potato Journal, 2013)
In a field experiment conducted at Kufri, peas, cowpea, bean, amaranthus and oats were evaluated as a rotational-cum-green manure crop for potato. At the time of potato planting, two more treatments, viz. FYM @ 15 t/ha and 100%NPK (control) were included without any previous green manuring. Doses of NPK were reduced to 50% where green manure crops were grown or FYM was added. Among all the green manure crops, maximum bio-mass was added by amaranthus (207.8 q/ha) followed by oats (107.2 q/ha) and minimum by cowpea (23.87 q/ha). The vegetative growth of plants in terms of number of shoots, compound leaves and haulms weight/plant were maximum in 100% NPK, followed by pea, FYM and cowpea. Maximum number of total and seed size (20-80g) tubers (5.60 and 4.36 lakh/ha, respectively) as well as maximum yields (326.9 and 275.7 q/ha, respectively) were obtained with FYM + 50% NPK followed by 100%NPK. Among the various green manure crops, bean+ 50% NPK resulted in maximum number of total tubers (4.58 lakh/ ha) as well as total yields (300.3 q/ha), which were statistically at par with those obtained with 100% NPK without green manuring. Whereas, peas +50% NPK gave highest number of seed size tubers (3.53 lakh/ha) as well as yield (235.4 q/ha). The results showed that growing beans / peas as a rotational-cum-green manure crop in seed potato fields will be beneficial for the farmers of the region to reduce the doses and thus the costs of fertilizers to half (50%) without compromising the potato yields. Whereas, addition of FYM @ 15t/ha along with 50% dose of NPK can be used profitably for the ware potato crop where rotation or green manuring practices are not followed.